Developing visitors' perception indicators on natural resource conservation in Tasik Kenyir, Malaysia - Nordin, Nurul Afifah; Shuib, Ahmad; Kunasekaran, Puvaneswaran; Abdullah, Nawal Hanim; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (IDOSI Publications, 2018)
The purpose of this paper is to develop scale to measure the indicators of the visitors’ perception on natural resources conservation for ecotourism development in Tasik Kenyir, Malaysia. Constructed questionnaires were distributed to visitors in Tasik Kenyir who were selected using the convenience sampling method which is a non-probability sampling technique. The data collection method used in this study was the face-to-face interview. Descriptive analysis was used to describe the socio-demographic profiles of the respondents in this study, while factor analysis was used to develop the scale for the visitors’ perception on natural resource conservation. Results obtained in this study indicate that 24 variables have significant contribution in determining the perception on the indicators of natural resource conservation and are distributed into nine factors. These findings can be used undertaking the conservation of natural resource for the development of ecotourism.